Knowledge and practices toward COVID-19 among healthcare students: A cross-sectional study at the University of Zambia - Mudenda, Steward; Ngalande, Nelly; Mukosha, Moses; Hikaambo, Christabel Nang'andu; Daka, Victor; Matafwali, Scott Kaba; Banda, Michelo; Mfune, Ruth Lindizyani; Mayoka, Godfrey; Witika, Bwalya Angel (Frontiers in Public Health, 2022)
Background The COVID-19 pandemic led to the disruption of physical classes for university students globally, as large gatherings fuelled the transmission of the virus. In the efforts to mitigate its transmission and return to normality, prevention measures, including vaccination, have been encouraged. Therefore, it is critical to understand the knowledge and practices of students regarding COVID-19. This study assessed the knowledge and practices toward COVID-19 among healthcare students at the University of Zambia. Materials and methods This questionnaire-based cross-sectional study was carried out from August 2021 to October 2021 among 478 healthcare students (pharmacy, physiotherapy, nursing, biomedical, medicine, and radiography). We used a previously validated questionnaire to measure knowledge and practice. The predictors of knowledge and practices were assessed using logistic regression with robust estimation of standard errors. Statistical analysis was conducted using Stata/BE version 17.0. Results Of the 478 respondents, 243 (50.8%) were females. A larger proportion, 175 (36.6%) were in Pharmacy training, and 156 (32.6%) were in their fifth year of study. The overall mean knowledge score of the participants was 87.9 (SD = 16.1), being higher at 89.6 (SD = 14.3) among medical students and the lowest at 86.7 (SD = 17.1) among Pharmacy students, although this was statistically non-significant (p = 0.488). The overall mean practice score was 60.0 (SD = 24.7), being significantly higher at 63.5 (23.4) among nursing, physiotherapy and environmental students compared to other students (p = 0.048). In multivariable analysis, the participant training program was non-significantly associated with knowledge and practice toward COVID-19. However, increased age (AOR = 1.09, 95% CI: 1.01–1.117) and residing in urban areas (AOR = 1.79, 95% CI: 1.07–3.01) than in rural areas were associated with higher odds of good practice toward COVID-19. Conclusion The healthcare students generally showed good knowledge levels and poor practices toward COVID-19. Further, there was no evidence of a difference in knowledge of COVID-19 among healthcare students. These findings suggest the need for implementation strategies to be centered on improving the practices of students toward COVID-19.